Implementation of The At-Tartil Method in Improving The Abilty to Read Al-Qur’an in The Ar-Rodhiyah Wonoayu Sidoarjo Qur’an Education Park (TPQ) - Agata, Rossalia; Nadlif, Ainun (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The ability to read the Qur'an is an important aspect of Islamic education and daily worship. In Indonesia, this teaching is carried out through institutions such as TPQ Ar-rodhiyah wonoayu, with standards involving the rules of ulumul tajweed and makharijul huruf. The At-tartil method, developed by the ma'arif nahdlatul ulama branch of sidoarjo, uses tartil rhythm-based techniques to improve the ability to read the Qur'an. This method is also known as the 3M method (listening, imitating, and seeing), where students are taught to listen, imitate and see, followed by repetition exercises (drill). This study aims to describe the application of the At-tartil method at TPQ Ar-Rodhiyah Wonoayu and the effectiveness of the At-tartil method in improving the ability to read the Qur'an of students at TPQ Ar-Rodhiyah.The research method used is descriptive qualitative, involving direct observation, in-depth interviews with teachers and students and analysis of learning documents.